COMPLEX EVALUATION OF THE EFFICIENCY OF ONLINE STORES IN ELECTRONIC COMMERCE - Меркулова, Т. В.; Лубенець, С. В.; Янголенко, А. А. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2019)
he problem of comprehensive assessment of the effectiveness of electronic retail in E-commerce, which would allow the researcher to draw more general conclusions about the technological and economic efficiency of the online store is considered. It is shown that the use of traditional indicators of trade efficiency is quite laborious and requires the search and analysis of a significant amount of source data, as well as the use of a wide range of calculation methods. In order to conduct a comprehensive assessment of the effectiveness of online stores it was proposed to use specific technological efficiency indicators that directly characterize e-business technologies as a modern form of customer service due to the features of its organizational, technical, software and technological support. The calculation of the integral indicator of efficiency is carried out on the basis of the Sherdani criterion.The analysis of specific indicators introduced by Sherdani was carried out, and the approaches and peculiarities of their definition and assessment were considered. A number of recommendations on the implementation of an integrated approach to quantifying the economic efficiency of E-commerce at retail enterprises based on the Sherdani integral criterion is provided. Comparative assessment of the technological performance indicators of arbitrarily selected electronic online stores of enterprises conducting their activities in the B2C e-commerce sector in Ukraine was carried out.According to the results of a comparative analysis for each selected online store, specific indicators of the Sherdani criterion were determined, and the values of integral indicators were calculated, which do not only determine the current complex technological and economic efficiency of each online store, but also indicate possible ways to improve them. On the basis of the studies conducted, a number of practical recommendations were tested on a comprehensive quantitative assessment of economic efficiency of using e-commerce systems and online stores, which can be proposed for the use in the practice of E-commerce enterprises in the B2C segment.